Randomized clinical study on radial artery compression time after elective coronary angiography - Maria Aparecida de Carvalho Campos; Claudia Maria Rodrigues Alves; Miriam Harumi Tsunemi; Maria Angélica Sorgini Peterlini; Ariane Ferreira Machado Avelar (Universidade de São Paulo, 2018)
Objective to compare two compression times of the radial artery after coronary angiography with customized compressive dressing regarding the occurrence of hemostasis and vascular complications. Method a randomized clinical study was carried out in patients undergoing elective transradial coronary angiography in two study groups: (G30), whose compressive dressing was maintained for 30 minutes, and (G60), whose compressive dressing was maintained for 60 minutes, both until the first evaluation of hemostasis. Variables related to patients, procedure, occurrence of hemostasis, and vascular complications were analyzed. Patency of the radial artery was assessed with Doppler vascular ultrasonography, immediately after removing the compressive dressing and 30 days after the procedure. Results the sample consisted of 152 patients in G30 and 151 in G60. Hemostasis was evidenced in the first evaluation in 76.3% of G30 patients and 84.2% of G60 patients (p = 0.063). There were 91 immediate complications, being 53 hematomas and 38 occlusions of the radial artery. We identified 18 late occlusions, 7 (5.5%) in G30 and 11 (8.2%) in G60. Conclusion the different compression times of the radial artery after coronary angiography did not significantly influence the occurrence of hemostasis and vascular complications. Brazilian Registry of Clinical Trials (Rebec): RBR-7VJYMJ.